Evaluation of myenteric neurons in the colon of rats exposed to 2,4 dichlorophenoxyacetic acid herbicide - Nanni, Wagner; Porto, Gisele da Silva; Pereira, Joice Naiara Bertaglia; Gonçalves, Alexandre Rodrigo Nascimento [UNESP]; Marinsek, Gabriela Pustiglione [UNESP]; Stabille, Sandra Regina; Favetta, Paula Montanhini; Germano, Ricardo de Melo; Mari, Renata de Britto [UNESP] (Taylor & Francis, 2022)
The assessment of the enteric nervous system provides a better understanding of the effects that contaminants can have on the health and well-being of organisms. It has been reported that 2,4-dichlorophenoxyacetic acid (2,4-D) is a highly persistent herbicide in the environment that is responsible for neurotoxic changes in different myenteric neuronal subpopulations. The current study aimed to evaluate the effects of 2,4-D on myenteric neurons in the colon of Rattus norvegicus for the first time. A dose of 2,4-D (5 mg/kg/day) was administered to the experimental group (2,4-D) for 15 days. Then, the proximal colon was collected and submitted to Giemsa and NADPH-d histochemical techniques for the disclosure of total and nitrergic neurons. The 2,4-D group presented a higher density of total neurons (p = 0.05, t-test), which together with the maintenance of nitrergic neuronal density, may be related to the increase in the expression of the neurotransmitter acetylcholine by colocalization, responsible for stimulating the intestinal smooth muscle and increasing the chances of the expulsion of the harmful content present in the lumen. Over 15 days, the neurotoxic effects of 2,4-D in the myenteric plexus influenced an increase in the general population of myenteric neurons in the colon.
Keywords: Agricultural defensive; intestine; myenteric plexus; neuronal plasticity; neurotoxicity